Artificial Intelligence in Graphic Design Processes: The Impact Analysis and Challenges (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
AbstractThe integration of Artificail Intelligence (AI, henceforth) in graphic design is more than just a revolution; it is an era-defining transformational wave that has completely altered the way things are done in the creative industry. This piece of research explores the broad impacts that AI has on graphic design— from being able to take care of repetitive tasks without any fuss all the way to helping designers discover new horizons in their creativity. It even looks into personalization through a comprehensive review that includes current AI technologies as well as literature and case studies available.We consider both sides when we talk about what role AI can play for us: opportunities it brings along with challenges we might face because of its implementation. Through a background review and analysis of current AI applications and tools, the study will highlight the potential benefits, challenges, and ethical issues associated with integrating AI into graphic design. The goal of this study is to help graphic design professionals make informed decisions about using AI in their work and shed light on the changing graphic design landscape and the impact that AI integration will have. The results of this study indicate that AI has a dual role to play in the field of design — while making design capabilities available to the masses, it also stirs up discussions on ethics through issues like whether automation can lead to job displacements or not? and where does one draw a line on creativity?As we draw our attention towards navigating through this constantly evolving landscape which is now being powered by AI at every step, let us try to understand how these technologies are not just changing production methodologies but redefining what art stands for, especially at a time like ours, when we find ourselves deep into this digital age.
Keywords: Artificial Intelligence (AI); Graphic Design Processes; AI-enhanced Graphic Design; AI Technologies